2017
DOI: 10.1016/j.ces.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Systematic model identification and optimization-based active polymorphic control of crystallization processes

Abstract: This is a repository copy of Systematic model identification and optimization-based active polymorphic control of crystallization processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…More recently, the kinetic model of solvent‐mediated transformation processes was extended to a hypothetical dimorphic system by considering additional crystallization mechanisms 15 . Accounting for the solvent‐mediated polymorphic transformation of ortho‐aminobenzoic acid, a PBE‐based polymorphic control strategy was developed for production of the stable polymorph 16 . Nonetheless, no PBE‐based studies can be found in the literature to model the crystallization process of concomitant polymorphism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the kinetic model of solvent‐mediated transformation processes was extended to a hypothetical dimorphic system by considering additional crystallization mechanisms 15 . Accounting for the solvent‐mediated polymorphic transformation of ortho‐aminobenzoic acid, a PBE‐based polymorphic control strategy was developed for production of the stable polymorph 16 . Nonetheless, no PBE‐based studies can be found in the literature to model the crystallization process of concomitant polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we utilized process modeling and simulation to bridge kinetic events, including nucleation and crystal growth, with a population balance equation (PBE) model. PBE models are widely used to simulate various crystallization processes, including solventmediated polymorphic transformation [13][14][15][16] and chiral resolution by preferential crystallization. 17,18 Both seeded and unseeded phase transformation processes of L-glutamic acid α-form to the stable β-form were described using a population balance model.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the combination of Raman spectroscopy and ATR-UV/Visible spectroscopy, Simone et al [40,83] developed active polymorphic feedback control (AFPC) and used it to perform hierarchical control to achieve crystal refining, as shown in the simple schematic diagram of the control strategy (Figure 9). Raman spectroscopy is used to detect the presence of the undesired form (P) by using a calibration-free approach; ATR-UV/Vis is used to measure the solute concentration (C) and performs SSC using a calibration-based approach to determine the set point for the temperature controller (Tsp).…”
Section: Polymorphic Feedback Controlmentioning
confidence: 99%
“…The bridging liquid is added, forming bridging liquid droplets under stirring due to the immiscibility between the bridging liquid and the mixture of solvent and anti‐solvent, which can effectively wet the individual crystals into spherical agglomerates 3 . Compared with the traditional granulation technology (Figure 1A), this technology (Figure 1B) significantly simplifies the equipment and process, achieving equipment space and cost savings, energy conservation, less carbon emission, consumption reduction, and reduced production cycle by over 40% 4–8 . Furthermore, the greatly enhanced powder properties of the spherical products achieve advanced functions, for example, direct tableting for drugs, 9–12 anti‐caking ability for food and fertilizers, 13 superior skin feeling for cosmetics, 14 high performance for explosives, 15–17 and so on.…”
Section: Introductionmentioning
confidence: 99%